Preparation method of high-wear-resistance outsole
By introducing multi-component rubber composite materials and dynamic crosslinking networks into the rubber outsole, the problem of existing rubber outsoles being prone to failure under dynamic stress and high-frequency wear conditions is solved, and the effect of significantly improving wear resistance, fatigue resistance and dynamic repair performance is achieved.
Patent Information
- Application Number
- CN202411989805.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-25
AI Technical Summary
The existing rubber soles are prone to failure under dynamic stress and high-frequency wear conditions, and have insufficient wear resistance and fatigue resistance.
Through the synergy of multi-component rubber composite materials, combined with the introduction of dynamic crosslinking networks, a composite network structure combining static crosslinking and dynamic crosslinking is constructed. The composition includes natural rubber, isoprene rubber, butadiene rubber, styrene-butadiene rubber, reinforcement fillers, dynamic crosslinking agents, plasticizers, vulcanizing agents and accelerators.
It significantly improves the wear resistance, fatigue resistance and dynamic repair performance of the material, so that the high wear-resistant soles maintain excellent performance under dynamic stress and high wear conditions, and is suitable for high-strength and high-frequency use scenarios.
Smart Images

Figure BDA0005223391570000161 
Figure BDA0005223391570000171 
Figure BDA0005223391570000191
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of rubber products, in particular to a method for preparing a highly wear-resistant outsole. Background Art
[0002] As an important component of footwear products, the performance of rubber outsoles directly affects the wear resistance, fatigue resistance and service life of the outsoles. In traditional technology, the manufacture of rubber outsoles is usually achieved by compounding natural rubber and synthetic rubber, supplemented by reinforcing fillers and vulcanizers to form a cross-linked network to improve the mechanical properties of the material. However, under dynamic stress and high-frequency wear conditions, the cross-linked network of traditional rubber materials is mainly static vulcanized bonds, lacking stress relief and damage repair capabilities, causing the material to easily crack and fail prematurely. At the same time, the single use of reinforcing fillers such as carbon black, although it can enhance the mechanical properties, is difficult to effectively improve the anti-slip performance in a slippery environment, limiting the overall performance of the outsole.
[0003] In addition, the multi-component rubber system of traditional outsole materials is usually unevenly proportioned or insufficiently optimized, which makes it difficult to achieve a balance between the material's wear resistance, flexibility, and dynamic fatigue performance. When the density of the static cross-linked network is too high, the material will show brittleness; and when the plasticizer or flexible component is excessive, the mechanical strength and durability of the material will be significantly reduced. In the prior art, the vulcanization process often ignores the dynamic control of pressure and temperature, which can easily lead to uneven distribution of the cross-linked network and further reduce the stability of the material. These technical limitations are particularly prominent in the field of high-performance soles, and there is an urgent need to overcome the above problems through innovative designs. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides a method for preparing a highly wear-resistant outsole, which solves the problems of the existing rubber outsole being prone to failure under dynamic stress and high-frequency wear conditions and having insufficient wear resistance and fatigue resistance.
[0005] To achieve the above objectives, the present invention is implemented through the following technical solutions:
[0006] The present invention provides a highly wear-resistant outsole composition, which significantly improves the wear resistance, fatigue resistance and dynamic repair performance of the material through the synergistic effect of a multi-component rubber composite material and the introduction of a dynamic cross-linking network. The composition comprises the following components in parts by mass:
[0007] Natural rubber (30-50 parts)
[0008] Natural rubber (NR) is the basic rubber matrix of the present invention, and has excellent elasticity, fatigue resistance and processing performance. Its molecular chain has a high crystallization ability, and when subjected to tension or dynamic stress, it forms a locally oriented crystallization area, providing excellent mechanical properties and initial wear resistance for the outsole. In addition, the molecular structure of natural rubber (cis-1,4-polyisoprene) can have good compatibility with other synthetic rubbers, thereby constructing a uniform composite network structure.
[0009] Isoprene rubber (15-30 parts)
[0010] Isoprene rubber (IR) is a synthetic rubber with a molecular structure similar to that of natural rubber. It is a cis-structured polymer with high molecular chain flexibility, which can enhance the tear resistance and wear resistance of composite materials. The addition of isoprene rubber makes up for the insufficient performance of natural rubber under dynamic fatigue conditions, and synergizes with natural rubber to effectively increase the service life of the material. In addition, the non-polar molecular chain structure of isoprene rubber can reduce the friction coefficient of the material, thereby reducing wear.
[0011] Butadiene rubber (15-30 parts)
[0012] Butadiene rubber (BR) is a high cis-polybutadiene with a low glass transition temperature (about -110°C), so it can still maintain high flexibility under low temperature conditions. Its molecular chain is more flexible and has a lower friction factor, which can effectively reduce the wear rate, thereby improving the wear resistance of the material. The high elongation and impact resistance of butadiene rubber also make it show stronger resistance to crack propagation under dynamic stress. Through the synergistic effect with natural rubber and isoprene rubber, the introduction of butadiene rubber significantly improves the stability and durability of the material under low temperature and high dynamic stress conditions.
[0013] Styrene-butadiene rubber (5-15 parts)
[0014] Styrene-butadiene rubber (SBR) is a block copolymer formed by the copolymerization of styrene and butadiene, with high wear resistance and good processing performance. The styrene group provides a certain rigid structure, which can improve the dimensional stability and processing performance of the material, while the butadiene segment provides flexibility and elasticity, optimizing the dynamic and static properties of the material. The molecular structure of SBR can also enhance the thermal stability of the composite material, making it exhibit excellent aging resistance under high temperature conditions.
[0015] Reinforcement filler (20-50 parts)
[0016] The reinforcing filler in the present invention mainly includes carbon black and white carbon black. The introduction of carbon black provides excellent wear resistance for the material. It forms a physical and chemical dual reinforcement structure through the interface with the rubber matrix, thereby improving the mechanical strength and wear resistance of the outsole. The high surface area and high activity of white carbon black can optimize the anti-slip performance of the material and further improve the uniformity of the reinforcement network. Through the synergistic effect of carbon black and white carbon black, the reasonable addition amount of reinforcing filler effectively enhances the wear resistance of the outsole and ensures the stability under dynamic conditions.
[0017] Dynamic crosslinking agent (0.5-5 parts)
[0018] The dynamic crosslinking agent introduces a dynamic crosslinking network structure in the present invention, the core of which is the construction of reversible crosslinking bonds (such as disulfide bonds or ester exchange bonds). Under the action of dynamic stress, the crosslinking bonds can be broken and re-formed, thereby alleviating stress concentration and avoiding crack propagation inside the material. The introduction of the dynamic crosslinking agent significantly improves the durability and crack resistance of the outsole, allowing it to maintain excellent performance stability under dynamic wear conditions.
[0019] Plasticizer (5-15 parts)
[0020] The main function of the plasticizer is to improve the processing properties of the rubber and increase the flexibility of the material. In the present invention, naphthenic oil is preferably used as a plasticizer, which can reduce the viscosity of the rubber system and improve the dispersion uniformity during the mixing process. In addition, naphthenic oil can also improve the low-temperature performance of the rubber, ensuring that the outsole is not easy to harden and crack in a low-temperature environment.
[0021] Vulcanizing agent (1-3 parts)
[0022] The vulcanizing agent is the core substance that forms a static cross-linking network during the vulcanization process of rubber. In the present invention, sulfur is preferably used as the vulcanizing agent, which forms a sulfur bond cross-linking structure with rubber molecules, providing a basic three-dimensional cross-linking network, thereby significantly improving the mechanical properties and durability of the material.
[0023] Accelerator (0.5-2 parts)
[0024] The main function of the accelerator is to accelerate the vulcanization reaction rate and improve the crosslinking efficiency. In the present invention, N-cyclohexyl-2-benzothiazole sulfenamide (CZ) or dithiocarbamate compounds (DM) are preferably used as accelerators, which can synergize with the vulcanizing agent to ensure that the crosslinking network is uniform and stable.
[0025] The present invention constructs a composite network structure combining static crosslinking and dynamic crosslinking through the composite ratio of natural rubber, isoprene rubber, butadiene rubber and styrene-butadiene rubber, and the optimized coordination of reinforcing fillers, dynamic crosslinking agents, vulcanization systems and additives.
[0026] The static cross-linked network provides basic mechanical properties and dimensional stability; the dynamic cross-linked network achieves stress relief and micro-damage repair through the breaking and recombination of reversible bonds; the dual reinforcement effect of the reinforcing filler enhances wear resistance and optimizes stability under dynamic wear conditions.
[0027] This technical solution enables the highly wear-resistant outsole to maintain excellent performance under dynamic stress and high wear conditions, and is suitable for high-intensity and high-frequency usage scenarios, such as sports shoe soles and industrial shoe sole manufacturing.
[0028] Preferably, the amount of carbon black added is 10 to 40 parts, and the amount of white carbon black added is 10 to 30 parts.
[0029] The reinforcing filler in the present invention mainly includes carbon black and white carbon black. As a traditional reinforcing filler, carbon black has excellent reinforcing performance. It can form a dual action mechanism of physical filling and chemical bonding through the interface with the rubber matrix, thereby significantly improving the mechanical properties and wear resistance of the rubber. After carbon black is dispersed in the rubber matrix, it can effectively increase the hardness and tensile strength of the outsole, enhance the rubber's ability to resist crack propagation, and further improve the wear life of the outsole during dynamic use.
[0030] As another reinforcing filler, silica has a rich surface of active hydroxyl structures, which can interact physically and chemically with the rubber matrix, thereby improving the uniformity and dynamic performance of the rubber composite material. The high specific surface area of silica can increase the contact area between the rubber and the filler, making the reinforcement effect more significant, while optimizing the grip performance of the material under wet and slippery conditions. Compared with carbon black, the introduction of silica can also improve the aging resistance and flexibility of the rubber, making the outsole show more stable performance in complex environments.
[0031] The synergistic effect of carbon black and white carbon black further improves the mechanical properties and wear resistance of the rubber outsole. Carbon black provides high wear resistance and high strength, while white carbon black optimizes the dynamic performance and anti-skid performance of the composite material. By controlling the ratio of carbon black and white carbon black, the addition amount of carbon black is 10 to 40 parts and the addition amount of white carbon black is 10 to 30 parts, the rubber composite material can achieve the best balance between wear resistance, anti-skid and dynamic stability, thereby significantly improving the overall performance of the outsole in different usage scenarios.
[0032] Preferably, the dynamic cross-linking agent is a compound containing a disulfide bond group.
[0033] The dynamic crosslinking agent in the present invention is preferably a compound containing a disulfide bond group. A disulfide bond (SS bond) is a reversible chemical bond, which has the characteristic of being able to break and reform under the action of external stress, heat or chemical environment. This characteristic gives the material the ability to self-repair under dynamic use conditions. Specifically, when the rubber outsole is subjected to dynamic stress or friction during use, the disulfide bonds inside the material will break to relieve stress concentration, thereby avoiding further expansion of local damage; when the stress is released, the broken disulfide bonds can be regenerated to restore the original integrity of the material.
[0034] The compound containing disulfide bond groups can not only form a dynamic cross-linking network, but also chemically cross-link with rubber molecular chains to improve the density and stability of the cross-linking network. This dynamic cross-linking network plays a dual role of stress dissipation and damage repair in the composite material of the present invention, significantly improving the wear resistance and crack resistance of the material.
[0035] By introducing a dynamic crosslinking agent containing disulfide bonds into the composition, the generation and expansion of cracks can be effectively slowed down during the dynamic use of the outsole, while extending the service life of the material. This dynamic crosslinking mechanism complements the static vulcanization crosslinking network and together constructs the high-performance rubber matrix of the present invention, providing the outsole with excellent wear resistance and dynamic stability.
[0036] Preferably, the dynamic cross-linking agent comprises one or more of a disulfide bond-containing compound, a thiol compound and an ester exchange catalyst.
[0037] The dynamic crosslinking agent in the present invention preferably includes one or more of a disulfide bond-containing compound, a thiol compound and an ester exchange catalyst. These dynamic crosslinking agents can participate in the construction of a crosslinking network through different chemical mechanisms, thereby significantly improving the mechanical properties and dynamic properties of the rubber composite material.
[0038] Compounds containing disulfide bonds build dynamic cross-linked networks through their reversible breaking and rebonding properties. When the material generates stress concentration under the action of external force, the disulfide bonds (SS bonds) break to disperse the stress, thereby avoiding local damage inside the material; when the stress is released, the disulfide bonds can be reformed to restore the structural integrity of the material, thereby providing self-repairing ability. Preferred disulfide-containing compounds are dibenzothiazole disulfide or diphenyl disulfide. These compounds can combine with rubber molecular chains, which not only enhances the stability of the cross-linked network, but also gives it dynamic response characteristics.
[0039] Thiol compounds such as mercaptoacetic acid or mercaptopropionic acid can react chemically with unsaturated double bonds in rubber to form additional crosslinking points. These crosslinking points have a certain degree of dynamic reversibility and can show a certain degree of fracture and reorganization under dynamic stress, which helps to further improve the stress relief ability and durability of the composite material. In addition, mercapto compounds can also work synergistically with other crosslinking agents to optimize the overall performance of the crosslinking network.
[0040] Transesterification catalysts such as titanates or organotin compounds introduce dynamically reversible ester bonds into the material by catalyzing transesterification reactions. These ester bonds exhibit the characteristics of breaking and rebonding under dynamic conditions, which complement the dynamic behavior of disulfide bonds and jointly improve the wear resistance and crack resistance of the rubber outsole under dynamic stress conditions.
[0041] Through the synergistic effect of disulfide-containing compounds, thiol compounds and transesterification catalysts, the constructed dynamic cross-linked network can achieve stress dispersion, crack slow release and damage repair during the use of the material, thereby significantly improving the comprehensive performance of the rubber outsole. This design enables the outsole material of the present invention to exhibit better wear resistance and service life under dynamic conditions, while maintaining its mechanical strength and processing stability.
[0042] Preferably, the plasticizer is cyclohexane oil, and the added amount is 5 to 10 parts.
[0043] As a non-polar plasticizer, naphthenic oil has good compatibility and dispersibility, and can be well miscible with rubber matrix molecules, thereby reducing the viscosity of the mixed rubber and improving the fluidity and dispersibility of the material during processing. Its introduction can not only optimize the processing performance of rubber, but also enhance the flexibility and low temperature resistance of rubber materials.
[0044] The naphthenic oil in the rubber matrix increases the slippage of the molecular chain through physical filling, thereby reducing the cohesive energy density between rubber molecules. This property can significantly improve the flexibility of the material during use, especially in low temperature environments, so that the rubber outsole maintains good elasticity and is not easy to crack. In addition, the appropriate addition of naphthenic oil can also improve the dynamic performance of the composite material, reduce the internal heat accumulation of the material under dynamic stress, and extend the service life.
[0045] By controlling the addition amount of cyclohexane oil within the range of 5 to 10 parts, the processing performance and use performance of the rubber can be significantly improved, and the mechanical properties of the material will not be reduced due to excessive addition, thereby providing excellent flexibility and stability for the high wear-resistant outsole of the present invention.
[0046] Preferably, the accelerator is N-cyclohexyl-2-benzothiazole sulfenamide or a dithiocarbamate compound.
[0047] This type of accelerator can work synergistically with vulcanizing agents (such as sulfur) during the vulcanization process to accelerate the cross-linking reaction between rubber molecules, improve the vulcanization efficiency, and thus build a uniform and stable cross-linking network.
[0048] N-cyclohexyl-2-benzothiazole sulfonamide (CZ) is a commonly used delayed-release accelerator. Its molecular structure has strong activation ability and can effectively prolong the scorch time of vulcanization, thereby providing a longer operating window for rubber mixing and processing. During the vulcanization process, CZ can evenly promote the cross-linking reaction between the vulcanizer and the rubber molecules, making the cross-linking network more evenly distributed and improving the mechanical properties of the material.
[0049] Dithiocarbamate compounds are fast accelerators that can quickly catalyze the activation of vulcanizers and promote the formation of sulfur bonds. These compounds are suitable for applications that require high vulcanization speed and crosslinking density. When used in conjunction with CZ, they can optimize the rate of the vulcanization process and the structure of the crosslinking network, ensuring the comprehensive performance of the material.
[0050] By using CZ or dithiocarbamate accelerators, precise control of the vulcanization reaction can be achieved to ensure the cross-linking uniformity and stability of the rubber material. Its application in the present invention significantly improves the mechanical properties and dynamic stability of the highly wear-resistant outsole, meeting the high performance requirements under complex use conditions.
[0051] Preferably, the vulcanizing agent is sulfur, and the added amount is 1.5 to 3 parts.
[0052] Sulfur, as the most commonly used vulcanizing agent in rubber vulcanization reactions, can react chemically with unsaturated double bonds in rubber molecules to form cross-linked bonds, thereby constructing a three-dimensional cross-linked network. This cross-linked network gives rubber materials excellent mechanical properties and dimensional stability.
[0053] During the vulcanization process, sulfur connects rubber molecular chains together through cross-linking reactions, thereby improving the strength, elasticity and fatigue resistance of the material. The sulfur bonds generated during the vulcanization process can enhance the interaction between rubber molecular chains at the molecular level, making the material exhibit high crack resistance and durability under tension, bending and dynamic load conditions. In addition, the right amount of sulfur can also ensure that the density of the cross-linked network is moderate, avoiding excessive cross-linking that leads to increased brittleness of the material.
[0054] By controlling the amount of sulfur added to 1.5 to 3 parts, the optimal balance of the vulcanization reaction can be achieved, so that the rubber outsole has good mechanical properties and dynamic stability while maintaining excellent wear resistance and flexibility. The amount of vulcanizer used within this range can ensure the uniformity of the cross-linked network and further improve the stability and service life of the material in complex use environments.
[0055] The present invention also provides a method for preparing a highly wear-resistant outsole, comprising the following steps:
[0056] (1) Mixing natural rubber, isoprene rubber, butadiene rubber and styrene-butadiene rubber with reinforcing fillers. The mixing temperature is controlled at 110-130°C for 6-10 minutes to ensure that the rubber matrix and the reinforcing fillers are fully mixed.
[0057] Through high temperature shearing, the reinforcing filler is evenly dispersed in the rubber matrix, thereby forming a good reinforcing network structure. In this step, the preferred order of addition is to first add carbon black and mix for 3 to 6 minutes, so that it is fully mixed with the rubber, and then add white carbon black and continue mixing for 3 to 4 minutes. This step-by-step addition method can avoid the aggregation of carbon black and white carbon black in the rubber matrix, ensure their uniform distribution, and enhance the mechanical properties of the composite material.
[0058] (2) After the first stage of mixing is completed, add the dynamic crosslinking agent and plasticizer and continue mixing. The temperature is controlled at 90 to 110° C. for 5 to 8 minutes.
[0059] The introduction of dynamic crosslinking agent is completed at this stage, and it can initially combine with rubber molecules to provide conditions for the subsequent formation of dynamic crosslinking network. The addition of plasticizer further reduces the viscosity of the compounded rubber and enhances its processing fluidity.
[0060] (3) Cool the mixed rubber material to 60-90°C, then add the vulcanizer and accelerator and mix at low temperature for 3-5 minutes.
[0061] During this stage, the vulcanizer and accelerator are evenly dispersed in the rubber, ensuring that a uniform three-dimensional cross-linked network can be formed during the vulcanization process. At the same time, the combination of the dynamic cross-linking agent and the vulcanization system can effectively achieve the synergistic effect of static cross-linking and dynamic cross-linking, thereby improving the wear resistance and fatigue performance of the product.
[0062] (4) The mixed rubber material is processed into a rubber sheet with a thickness of 3 to 10 mm through a calendering process.
[0063] The calendering process requires controlling the temperature and pressure of the calender to ensure that the thickness of the sheet is uniform and the surface is smooth, providing high-quality semi-finished products for subsequent vulcanization.
[0064] (5) placing the calendered sheet into a vulcanization mold for vulcanization treatment, the vulcanization temperature is controlled at 140-160° C., the vulcanization time is 10-15 minutes, and the vulcanization pressure is 8-12 MPa.
[0065] Preferably, the vulcanization mold adopts a staged pressurization mode during the vulcanization process, that is, a lower pressure is applied at the initial stage of vulcanization, and then the pressure is gradually increased when the vulcanization reaction reaches a certain degree, and the process is completed in two stages, and the duration of each stage is 50% of the total vulcanization time. This pressurization mode can ensure the gradual formation of the cross-linked network, while avoiding bubble residue or product surface defects caused by excessive initial pressure, thereby improving the quality and performance of the finished product.
[0066] (6) After vulcanization, the product is cooled to room temperature and trimmed to obtain the finished outsole. The cooling process is completed by natural cooling or water cooling to ensure that the product size is stable and the internal stress is completely released.
[0067] The preparation method of the present invention ensures the uniformity of the internal cross-linking network of the material and the optimization of dynamic performance through a reasonable raw material mixing sequence, a dynamic cross-linking agent addition stage and a staged vulcanization process, so that the prepared high wear-resistant outsole has significant advantages in wear resistance, fatigue resistance and service life.
[0068] The present invention provides a method for preparing a highly wear-resistant outsole. It has the following beneficial effects:
[0069] 1. The present invention effectively constructs a high-strength reinforcement network by rationally mixing natural rubber, isoprene rubber, butadiene rubber and styrene-butadiene rubber, and combining the synergistic effect of reinforcing fillers (carbon black and white carbon black), so that the outsole exhibits excellent wear resistance during dynamic use. Carbon black provides high wear resistance and mechanical strength, and white carbon black improves grip performance and dynamic stability in wet and slippery environments, so that the outsole has a longer service life under complex use conditions.
[0070] 2. The present invention introduces a dynamic crosslinking agent to construct a dynamic crosslinking network, and combines it with a static vulcanization crosslinking network to form a dynamic-static composite crosslinking structure. Dynamic crosslinking agents (such as compounds containing disulfide bonds) achieve stress relief and self-repair when the material is subjected to dynamic stress or crack propagation through reversible fracture and rebonding, significantly enhancing the fatigue resistance of the outsole. This dynamic response mechanism allows the outsole to maintain structural integrity during long-term use and avoid early failure caused by stress concentration.
[0071] 3. The present invention adopts a reasonable preparation process, especially through staged mixing, step-by-step addition of dynamic crosslinking agent and staged pressurization mode of vulcanization mold, so that reinforcing filler, vulcanizing agent and dynamic crosslinking agent are evenly dispersed in the rubber matrix, ensuring the uniformity of the crosslinking network and the optimization of dynamic performance. Staged pressurization vulcanization effectively avoids bubble residue and material defects, further improves the quality stability of the product, and provides a reliable guarantee for the industrial production of high wear-resistant outsole. DETAILED DESCRIPTION
[0072] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0073] Embodiment 1:
[0074] Formula composition (by mass):
[0075] Natural rubber (NR): 40 parts
[0076] Isoprene rubber (IR2200): 20 parts
[0077] Butadiene rubber (BR9000): 20 parts
[0078] Styrene-butadiene rubber (SBR1502): 10 parts
[0079] Carbon black (N330): 25 parts
[0080] White carbon black: 15 parts
[0081] Dynamic crosslinking agent (benzothiazole disulfide): 2 parts
[0082] Naphthenic oil: 8 parts
[0083] Sulfur: 2 parts
[0084] Accelerator (CZ): 1 part
[0085] Preparation method:
[0086] (1) mixing natural rubber, isoprene rubber, butadiene rubber, styrene-butadiene rubber and carbon black at a temperature of 120° C., adding white carbon black after mixing for 6 minutes, and continuing mixing for 4 minutes;
[0087] (2) adding a dynamic crosslinking agent and cyclohexane oil, and continuing to mix, with the temperature controlled at 100° C. for 6 minutes;
[0088] (3) cooling to 80° C., adding sulfur and accelerator, and mixing for 3 minutes to obtain a rubber mix;
[0089] (4) rolling the rubber mixture into a sheet with a thickness of 5 mm;
[0090] (5) Place the sheet into a vulcanization mold and vulcanize at 150°C and 10 MPa for 12 minutes;
[0091] (6) Cooling and trimming to obtain the finished outsole.
[0092] Embodiment 2:
[0093] Formula composition (by mass):
[0094] Natural rubber (NR): 35 parts
[0095] Isoprene rubber (IR2200): 25 parts
[0096] Butadiene rubber (BR9000): 15 parts
[0097] Styrene-butadiene rubber (SBR1502): 15 parts
[0098] Carbon black (N660): 20 parts
[0099] White carbon black: 20 parts
[0100] Dynamic crosslinker (thioglycolic acid): 3 parts
[0101] Naphthenic oil: 7 parts
[0102] Sulfur: 2.5 parts
[0103] Accelerator (DM): 0.8 parts
[0104] Preparation method:
[0105] (1) mixing natural rubber, isoprene rubber, butadiene rubber and carbon black at a temperature of 125° C. for 7 minutes; adding white carbon black and continuing mixing for 3 minutes;
[0106] (2) adding a dynamic crosslinking agent and cyclohexane oil and continuing to mix at a temperature of 95° C. for 5 minutes;
[0107] (3) Cool the rubber mixture to 70°C, add sulfur and accelerator, and mix for 3 minutes;
[0108] (4) rolling the rubber mixture into a sheet with a thickness of 4 mm;
[0109] (5) Place the sheet into a vulcanization mold and vulcanize it under pressure in stages: 8 MPa in the initial stage and 12 MPa in the later stage, 6 minutes in each stage, and a total vulcanization time of 12 minutes;
[0110] (6) Cooling and trimming to obtain the outsole.
[0111] Embodiment 3:
[0112] Formula composition (by mass):
[0113] Natural rubber (NR): 50 parts
[0114] Isoprene rubber (IR2200): 15 parts
[0115] Butadiene rubber (BR9000): 15 parts
[0116] Styrene-butadiene rubber (SBR1502): 10 parts
[0117] Carbon black (N550): 30 parts
[0118] White carbon black: 10 parts
[0119] Dynamic crosslinking agent (titanate): 1.5 parts
[0120] Naphthenic oil: 6 parts
[0121] Sulfur: 1.8 parts
[0122] Accelerator (CZ): 1 part
[0123] Preparation method:
[0124] (1) mixing natural rubber, isoprene rubber, butadiene rubber and carbon black at a temperature of 120° C. for 7 minutes; adding white carbon black and continuing mixing for 3 minutes;
[0125] (2) adding a dynamic crosslinking agent and cyclohexane oil and continuing to mix at a temperature of 95° C. for 5 minutes;
[0126] (3) Cool down to 75°C, add sulfur and accelerator, and mix for 3 minutes;
[0127] (4) rolling the rubber mixture into a sheet with a thickness of 6 mm;
[0128] (5) Place the sheet into a vulcanization mold and vulcanize at 155°C and 10 MPa for 15 minutes;
[0129] (6) Cooling and trimming to obtain the outsole.
[0130] Embodiment 4:
[0131] Formula composition (by mass):
[0132] Natural rubber (NR): 30 parts
[0133] Isoprene rubber (IR2200): 30 parts
[0134] Butadiene rubber (BR9000): 20 parts
[0135] Styrene-butadiene rubber (SBR1502): 10 parts
[0136] Carbon black (N330): 20 parts
[0137] White carbon black: 20 parts
[0138] Dynamic crosslinking agent (diphenyl disulfide): 3 parts
[0139] Naphthenic oil: 8 parts
[0140] Sulfur: 2 parts
[0141] Accelerator (DM): 0.8 parts
[0142] Preparation method:
[0143] (1) mixing natural rubber, isoprene rubber, butadiene rubber and carbon black at a temperature of 125° C. for 6 minutes; adding white carbon black and continuing mixing for 4 minutes;
[0144] (2) adding a dynamic crosslinking agent and naphthenic oil and continuing to mix at a temperature of 100° C. for 5 minutes;
[0145] (3) Cool down to 70°C, add sulfur and accelerator, and mix for 3 minutes;
[0146] (4) rolling the rubber mixture into a sheet with a thickness of 5 mm;
[0147] (5) Place the sheet into a vulcanization mold and vulcanize at 150°C and 12 MPa for 12 minutes;
[0148] (6) Cooling and trimming to obtain the outsole.
[0149] Embodiment 5:
[0150] Formula composition (by mass): Natural rubber (NR): 45 parts
[0151] Isoprene rubber (IR2200): 20 parts
[0152] Butadiene rubber (BR9000): 20 parts
[0153] Styrene-butadiene rubber (SBR1502): 15 parts
[0154] Carbon black (N660): 25 parts
[0155] White carbon black: 15 parts
[0156] Dynamic crosslinking agent (mercaptopropionic acid): 2.5 parts
[0157] Naphthenic oil: 9 parts
[0158] Sulfur: 2.2 parts
[0159] Accelerator (CZ): 0.9 parts
[0160] Preparation method:
[0161] (1) mixing natural rubber, isoprene rubber, butadiene rubber and carbon black at a temperature of 120° C. for 6 minutes; adding white carbon black and continuing mixing for 4 minutes;
[0162] (2) adding dynamic crosslinking agent and cyclohexane oil, and continuing to mix, and continuing to mix at a temperature of 95° C. for 5 minutes;
[0163] (3) Cooling to 80°C, adding sulfur and accelerator, and mixing for 3 minutes;
[0164] (4) rolling the rubber mixture into a sheet with a thickness of 6 mm;
[0165] (5) Place the sheet into a vulcanization mold and vulcanize at 145°C and 10 MPa for 14 minutes;
[0166] (6) Cooling and trimming to obtain the outsole.
[0167] Embodiment 6:
[0168] Formula composition (by mass):
[0169] Natural rubber (NR): 40 parts
[0170] Isoprene rubber (IR2200): 25 parts
[0171] Butadiene rubber (BR9000): 20 parts
[0172] Styrene-butadiene rubber (SBR1502): 15 parts
[0173] Carbon black (N330): 30 parts
[0174] White carbon black: 10 parts
[0175] Dynamic crosslinking agent (organic tin compound): 3 parts
[0176] Naphthenic oil: 7 parts
[0177] Sulfur: 2 parts
[0178] Accelerator (DM): 1 part
[0179] Preparation method:
[0180] (1) mixing natural rubber, isoprene rubber, butadiene rubber and carbon black at a temperature of 125° C. for 7 minutes; adding white carbon black and continuing mixing for 3 minutes;
[0181] (2) adding a dynamic crosslinking agent and cyclohexane oil, and continuing to mix, and continuing to mix at a temperature of 100° C. for 6 minutes;
[0182] (3) Cool down to 75°C, add sulfur and accelerator, and mix for 3 minutes;
[0183] (4) rolling the rubber mixture into a sheet with a thickness of 5 mm;
[0184] (5) Place the sheet into a vulcanization mold and vulcanize at 150°C and 8 MPa for 12 minutes;
[0185] (6) Cooling and trimming to obtain the outsole.
[0186] Comparative Example 1:
[0187] Same as Example 1, but without adding dynamic cross-linking agent.
[0188] Comparative Example 2:
[0189] The same as Example 2, but the ratio of carbon black to white carbon black in the reinforcing filler is adjusted to 35 parts of carbon black and 5 parts of white carbon black.
[0190] Comparative Example 3:
[0191] The same as Example 3, but the ratio of isoprene rubber to butadiene rubber is adjusted to 10 parts of isoprene rubber and 30 parts of butadiene rubber.
[0192] Test Example 1:
[0193] The test is carried out in accordance with GB / T 9867-2008 “Determination of wear resistance of vulcanized rubber or thermoplastic rubber”.
[0194] The test equipment used was a DI N wear tester, model: DI N Abrader-I II.
[0195] The test specimens were prepared as standard specimens according to the requirements of GB / T 9867-2008. The cylindrical specimens were 16 mm in diameter and 6 mm in thickness. They were cut from Example 1, Example 2, Comparative Example 1, and Comparative Example 2, respectively. Each specimen was tested 3 times and the average value was taken.
[0196] The experimental conditions are:
[0197] Friction wheel: DI N standard rolling grinding wheel;
[0198] Load: 10N;
[0199] Friction distance: 40m;
[0200] Ambient temperature: 23℃±2℃;
[0201] Rotation speed: 40rpm.
[0202] Experimental steps:
[0203] 1. Install the sample on the D IN wear tester to ensure that the contact surface between the sample and the grinding wheel is uniform;
[0204] 2. Set the test load to 10N, the friction distance to 40m, and start the testing machine;
[0205] 3. After the friction is completed, remove the sample and weigh the mass loss of the sample using a high-precision electronic balance (accuracy 0.001g);
[0206] 4. Calculate the wear amount of the sample;
[0207] 5. Repeat the test 3 times for each sample and take the average value.
[0208] The test results are shown in Table 1:
[0209] Table 1 Comparison of wear loss in DI N wear resistance test
[0210]
[0211]
[0212] The test results of Test Example 1 show that the embodiments of the present invention are significantly better than the comparative examples in terms of wear resistance, verifying the key role of the introduction of dynamic crosslinking agents and the reasonable ratio of multi-component rubber systems in improving wear resistance. The wear loss of Examples 1 and 2 is relatively low, which is due to the dynamic crosslinking network structure formed by the dynamic crosslinking agent in the rubber matrix. During the dynamic wear process, the dynamic crosslinking network can achieve stress relief through the breaking and recombination of disulfide bonds, avoiding premature failure of the material caused by local stress concentration. At the same time, the dynamic crosslinking network also gives the material a certain self-repairing ability, so that crack propagation is effectively suppressed, thereby further reducing the wear loss of the material. In contrast, no dynamic crosslinking agent was added to Comparative Example 1, and the crosslinking network was only composed of static vulcanized bonds, which could not cope with the stress concentration phenomenon under dynamic wear conditions, resulting in a significant increase in wear loss.
[0213] In addition, the reinforcing filler ratio of the present invention further improves the wear resistance of the rubber material. The synergistic effect of carbon black and white carbon black in the embodiment can form a uniform reinforcing network structure in the rubber matrix. Carbon black provides excellent mechanical strength and wear resistance, while white carbon black optimizes the dynamic performance and anti-skid performance of the material. The content of white carbon black in Comparative Example 2 is too low, resulting in an imbalance in the reinforcement system and an inability to form an efficient filler network, thus showing a higher wear amount. The experimental results show that the introduction of a dynamic cross-linked network and a reasonable ratio of reinforcing fillers have a synergistic effect in improving wear resistance, which is the core technical advantage of the present invention.
[0214] Test Example 2:
[0215] Dynamic fatigue test of rubber materials is carried out according to GB / T 13934 standard.
[0216] Experimental equipment and conditions:
[0217] Equipment: De Mattia fatigue testing machine;
[0218] Test frequency: 5Hz;
[0219] Bending angle: 90°;
[0220] Load: 2N;
[0221] Test time: 50,000 cycles;
[0222] Specimen type: dumbbell specimen (ASTM D412 standard), the length of the middle cut of the specimen is 1mm;
[0223] Environmental conditions: Normal temperature (23℃±2℃).
[0224] Experimental specimens:
[0225] Example 1, Comparative Example 1 (without dynamic crosslinking agent).
[0226] Experimental steps:
[0227] 1. Sample preparation:
[0228] Standard dumbbell-shaped specimens were cut from the sheets of the embodiments and comparative examples, and a 1 mm long incision was made in the middle of the specimen using a special cutter to ensure that the incision was uniform and free of burrs.
[0229] 2. Equipment Setup:
[0230] Set the fatigue testing machine to the following parameters:
[0231] Test frequency: 5Hz;
[0232] Bending angle: 90°;
[0233] Load: 2N;
[0234] Number of cycles: 50,000 times.
[0235] 3. Test operation:
[0236] Fix the specimen in the testing machine fixture, making sure the cut is located in the area with the maximum applied stress;
[0237] Start the testing machine and perform dynamic fatigue cycle test under set conditions.
[0238] 4. Crack measurement:
[0239] Stop the test after every 10,000 cycles, measure the crack length (unit: mm) using a microscope, record the data and continue the test;
[0240] The test was terminated after 50,000 cycles and the final crack length was recorded.
[0241] 5. Repeat the test:
[0242] The test was repeated 3 times for each sample and the average value was taken as the final result.
[0243] The test results are shown in Table 2:
[0244] Table 2 Dynamic fatigue crack growth test results of the embodiments and comparative examples
[0245]
[0246] Experimental results show that a reasonable amount of dynamic cross-linking agent, rubber component ratio and filler system are the core elements for achieving excellent dynamic fatigue performance. The present invention significantly improves the dynamic stability and service life of the rubber outsole by optimizing these aspects.
[0247] Test Example 3:
[0248] The test was carried out in accordance with GB / T 3962-2016 “Method for determination of friction coefficient of rubber”.
[0249] Experimental equipment and conditions:
[0250] Equipment: Friction coefficient tester;
[0251] Test medium: The surface is covered with 0.5mm water film;
[0252] Load: 5N;
[0253] Sliding speed: 0.1m / s;
[0254] Sample size: 10cm×10cm, thickness 6mm;
[0255] Environmental conditions: Normal temperature (23℃±2℃).
[0256] Experimental specimens:
[0257] Example 2, Comparative Example 2 (the ratio of reinforcing filler is unreasonable, 35 parts of carbon black and 5 parts of white carbon black).
[0258] Experimental steps:
[0259] 1. Sample preparation:
[0260] A standard sample of 10 cm×10 cm with a thickness of 6 mm was cut from the sheets of the embodiments and comparative examples, and the surface of the sample was ensured to be flat and smooth.
[0261] 2. Equipment debugging:
[0262] Adjust the friction coefficient tester to the following parameters:
[0263] Load: 5N;
[0264] Sliding speed: 0.1m / s;
[0265] Test medium: Water film thickness is 0.5mm.
[0266] 3. Test operation:
[0267] Evenly spread a 0.5mm thick water film on the test bench to simulate a slippery surface;
[0268] Fix the sample on the tester fixture and apply 5N pressure;
[0269] Start the tester, record the friction between the sample and the test table according to the set sliding speed, and calculate the friction coefficient.
[0270] 4. Repeat the test:
[0271] Each sample was tested 5 times and the average value was taken as the final result.
[0272]
[0273] In the present invention, the high specific surface area and surface active hydroxyl structure of white carbon black can form a strong interaction with the rubber molecules, increase the actual contact area between the rubber matrix and the slippery surface, and thus improve the friction coefficient in a slippery environment. At the same time, carbon black, as a traditional reinforcing filler, provides excellent mechanical strength and rigid support, and works together with white carbon black to form a uniform filler network structure. Such a network structure can not only improve the anti-slip performance of the rubber material, but also maintain good stability in a dynamic environment.
[0274] In contrast, the insufficient content of white carbon black in Comparative Example 2 destroyed the synergistic mechanism of the reinforcing filler, resulting in a significant decrease in anti-skid performance; while Comparative Example 7 did not use white carbon black at all, and carbon black reinforcement alone could not optimize the contact characteristics of the slippery surface, showing the lowest friction coefficient. This result shows that white carbon black plays an indispensable role in improving the friction coefficient in slippery environments, and the reasonable ratio of carbon black to white carbon black is crucial to achieving comprehensive performance. The present invention successfully balances the mechanical properties and dynamic grip performance of rubber through the scientific ratio of reinforcing fillers, significantly improves the anti-skid ability under slippery conditions, and further verifies the innovation and practicality of material design.
[0275] Test Example 4:
[0276] Tensile strength test: in accordance with GB / T 528-2009 "Determination of tensile properties of vulcanized rubber or thermoplastic rubber";
[0277] Tear strength test: in accordance with GB / T 529-2008 "Determination of tear strength of vulcanized rubber or thermoplastic rubber".
[0278] Experimental equipment and conditions:
[0279] Equipment: Electronic universal testing machine;
[0280] Tensile strength test:
[0281] Specimen type: dumbbell-shaped specimen (Type 2, GB / T 528-2009);
[0282] Stretching speed: 500mm / min;
[0283] Tear strength test:
[0284] Specimen type: right-angle specimen (GB / T 529-2008);
[0285] Stretching speed: 500mm / min;
[0286] Sample size: thickness 6mm;
[0287] Environmental conditions: normal temperature (23℃±2℃), relative humidity 50%±5%.
[0288] Experimental specimens:
[0289] Example 3 and Comparative Example 3 (unbalanced ratio of rubber components).
[0290] Experimental steps:
[0291] 1. Tensile strength test:
[0292] 1) Sample preparation:
[0293] Dumbbell-shaped specimens (type 2, GB / T 528-2009) with a thickness of 6 mm were cut from the sheets of the examples and comparative examples, and the surface of the specimens was ensured to be flat and free of defects.
[0294] 2) Equipment debugging:
[0295] Adjust the universal testing machine parameters:
[0296] Clamp spacing: 115mm;
[0297] Stretching speed: 500mm / min;
[0298] 3) Test operation:
[0299] Clamp both ends of the specimen in the upper and lower clamps of the testing machine respectively, ensuring that they are firmly clamped;
[0300] Start the equipment, stretch the specimen until it breaks, and record the maximum tensile stress (unit: MPa);
[0301] Each sample was tested 3 times and the average value was taken as the final result.
[0302] 2. Tear strength test:
[0303] 1) Sample preparation:
[0304] A right-angle specimen (GB / T 529-2008) with a thickness of 6 mm was cut from the sheets of the examples and comparative examples, and the cut was ensured to be smooth and free of burrs.
[0305] 2) Equipment debugging:
[0306] Adjust the universal testing machine parameters:
[0307] Stretching speed: 500mm / min;
[0308] 3) Test operation:
[0309] Fix the specimen in the testing machine fixture, making sure the fixture is aligned;
[0310] Start the equipment, stretch the sample until it is completely torn, and record the tear strength (unit: kN / m);
[0311] Each sample was tested 3 times and the average value was taken as the final result.
[0312] The test results are shown in Table 4:
[0313] Table 4 Comprehensive mechanical properties test results of the embodiments and comparative examples
[0314] Sample No. Tensile strength(MPa) Tear strength (kN / m) Example 3 24.5 80.6 Comparative Example 3 20.8 70.3
[0315] In contrast, due to the imbalance of the rubber component ratio, the synergistic effect between the multi-component rubbers was lost in Comparative Example 3, resulting in a significant decrease in tensile strength and tear strength, indicating that the reasonable ratio of the multi-component rubber is crucial to balancing the rigidity and flexibility of the material. The experimental results show that the present invention successfully achieves high strength, high toughness and high durability of the rubber outsole through the introduction of a dynamic cross-linking network, the optimized ratio of the multi-component rubber and the reasonable control of the amount of the vulcanizing agent, which is significantly better than the prior art.
[0316] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A highly wear-resistant outsole, characterized in that: It includes the following components in parts by mass: 30-50 parts of natural rubber; 15-30 parts of isoprene rubber; Butadiene rubber 15-30 parts; 5-15 parts of styrene-butadiene rubber; 20 to 50 parts of reinforcing filler; 0.5-5 parts of dynamic crosslinking agent; 5-15 parts of plasticizer; 1 to 3 parts of vulcanizing agent; Accelerator 0.5 to 2 parts.
2. The highly wear-resistant outsole according to claim 1, characterized in that: The reinforcing filler comprises carbon black and white carbon black, wherein the added amount of carbon black is 10 to 40 parts, and the added amount of white carbon black is 10 to 30 parts.
3. The highly wear-resistant outsole according to claim 1, characterized in that: The dynamic cross-linking agent is a compound containing a disulfide bond group.
4. The highly wear-resistant outsole according to claim 1, characterized in that: The dynamic crosslinking agent includes one or more of a disulfide bond-containing compound, a thiol compound and an ester exchange catalyst, wherein the disulfide bond-containing compound is dibenzothiazole disulfide or diphenyl disulfide, the thiol compound is thioglycolic acid or thiopropionic acid, and the ester exchange catalyst is titanate or an organic tin compound.
5. The highly wear-resistant outsole according to claim 1, characterized in that: The plasticizer is cycloalkane oil, and the added amount is 5 to 10 parts.
6. The highly wear-resistant outsole according to claim 1, characterized in that: The accelerator is N-cyclohexyl-2-benzothiazole sulfenamide or dithiocarbamate compound.
7. The highly wear-resistant outsole according to claim 1, characterized in that: The vulcanizing agent is sulfur, and the added amount is 1.5 to 3 parts.
8. A method for preparing a highly wear-resistant outsole, comprising preparing the highly wear-resistant outsole as claimed in any one of claims 1 to 7, characterized in that: The following steps are involved: (1) mixing natural rubber, isoprene rubber, butadiene rubber, styrene-butadiene rubber and reinforcing filler at a temperature of 110 to 130° C. for 6 to 10 minutes; (2) adding a dynamic crosslinking agent and a plasticizer and continuing to mix at a temperature of 90 to 110° C. for 5 to 8 minutes; (3) After cooling, add the vulcanizing agent and accelerator, mix until uniform, the temperature is 60-90°C, and the time is 3-5 minutes; (4) calendering the mixed rubber material to obtain a rubber sheet with a thickness of 3 to 10 mm; (5) placing the rubber sheet into a vulcanization mold, the vulcanization temperature is 140-160° C., the vulcanization time is 10-15 minutes, and the vulcanization pressure is 8-12 MPa; (6) Cooling and trimming to obtain a finished outsole.
9. The method for preparing a highly wear-resistant outsole according to claim 8, characterized in that: In step (1), the order of adding the reinforcing filler is to first add carbon black, mix for 3 to 6 minutes, then add white carbon black, and continue mixing for 3 to 4 minutes.
10. The method for preparing a highly wear-resistant outsole according to claim 8, characterized in that: The vulcanization mold in step (5) adopts a staged pressurization mode during the vulcanization process, with a pressure variation range of 8 to 12 MPa, and is completed in two stages, with each stage lasting 50% of the total vulcanization time.
Citation Information
Cited By
Preparation method of hard rubber
CN121108596A
A method for preparing hard rubber
CN121108596B